In situ synthesis of Pt nanoparticles in SBA-15 by encapsulating in modified template micelles: size restricted growth within the mesochannels - Prashar, Atul K.; Hodgkins, Robert P.; Kumar, Rajiv; Devi, R. Nandini (Journal of Materials Chemistry, 2008)
A truly in situ and simple method is developed for nanoparticle incorporation within the mesochannels of SBA-15 involving dispersion of metal precursors in surfactant-modified polymer micelles. The diffusion of the precursor within the micellar structure is aided by interaction with the cationic head group of the surfactant leading to a unique method to facilitate the formation of highly disperse, uniform nanoparticles molded by the walls of the mesochannels. The nanoparticle incorporated mesoporous material has a highly enhanced surface area and adsorption capabilities in comparison to its parent materials without any pore blockage which makes this method ideal for the preparation of nanocatalysts.

In situ encapsulation of pt nanoarchitectures of varying morphologies in mesoporous compounds - Prashar, Atul K.; Hodgkins, Robert P.; Chandran, Jima N.; Rajamohanan, P. R.; Devi, R. Nandini (Chemistry of Materials, 2010)
Nanoparticle morphology could be engineered and fine-tuned based on a novel in situ template method Different shapes of platinum nanoparticles were obtained from very low concentrations of precursors and could be isolated exclusively inside the mesochannels of SBA-15 This was achieved by dispersing a platinum precursor in surfactant modified polymer to different extents and using these composite materials as templates for the formation of mesoporous silica [PtCl(6)](2-) interacts with the cationic headgroup of the surfactant and facilitates the isolation of precursors within the composite template leading to the formation of nanoparticles molded by the walls of the mesochannels when calcined When this [PtCl(6)](2-)-surfactant-polymer micelle composite is aged for different duration, Pt nanoparticles of various morphologies like spheroids, nano rugby balls, and nanorods are obtained

In situ encapsulation of Pt nanoparticles in mesoporous silica: synthesis, characterisation and effect of particle size on CO oxidation - Prashar, Atul K.; Mayadevi, S.; Rajamohanan, P. R.; Devi, R. Nandini (Applied Catalysis A-General, 2011)
Pt nanoparticles of narrow size distribution and average particle size of 4.4 nm are isolated exclusively inside SBA-12 mesoporous silica by a novel in situ method. The interaction of Pt precursor with surfactant-polymer composite micelle is followed by NMR and UV studies. The final Pt incorporated silica material is characterised by XRD, TEM and N(2) adsorption. The mesoporous nature of the silica is found to be intact after Pt incorporation without any pore blockage. CO oxidation activity of this material is compared with that of mesoporous silica incorporating different sizes of Pt viz., 1.8, 3.6 and 8 nm. Activation energies of CO oxidation for all these materials are calculated by a simple differential method based on first principles. A comparison of activation energies and single site yields reveals that these parameters are distinguishably less in catalyst containing 1.8 nm Pt nanoparticles but more or less same in catalysts containing 3.6, 4.4 and 8 nm Pt nanoparticles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; In situ synthesis; Mesoporous silica; Pt nanoparticle